2017
DOI: 10.1136/archdischild-2017-313037
|View full text |Cite
|
Sign up to set email alerts
|

Chest compression during sustained inflation versus 3:1 chest compression:ventilation ratio during neonatal cardiopulmonary resuscitation: a randomised feasibility trial

Abstract: Clinicaltrials.gov NCT02083705, pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…A similar observation was reported during chest recoil after the application of a downward force on the chest of infants undergoing surgery requiring general anesthesia [29]. Additionally, the first randomized controlled trial comparing CC+SI and 3:1 C:V in preterm infants <33 weeks' gestation during neonatal resuscitation in the delivery room used a distending pressure of 24 cmH 2 O reported adequate V T delivery [30]. All of the aforementioned studies suggest the optimal PIP for CC+SI is approximately 20-25 cmH 2 O.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A similar observation was reported during chest recoil after the application of a downward force on the chest of infants undergoing surgery requiring general anesthesia [29]. Additionally, the first randomized controlled trial comparing CC+SI and 3:1 C:V in preterm infants <33 weeks' gestation during neonatal resuscitation in the delivery room used a distending pressure of 24 cmH 2 O reported adequate V T delivery [30]. All of the aforementioned studies suggest the optimal PIP for CC+SI is approximately 20-25 cmH 2 O.…”
Section: Discussionsupporting
confidence: 66%
“…Although there were more piglets that achieved ROSC following resuscitation with CC+SI_PIP_20, this was not significantly different compared to using CC+SI_PIP_10 and CC+SI_PIP_30. During CC+SI, improved carotid blood flow, mean arterial pressure, % change in ejection fraction, cardiac output, alveolar oxygen delivery and lung aeration may all result in faster ROSC by increasing intrathoracic pressure and improving minute ventilation [18][19][20][21]30]. In our study there were significant differences in minute ventilation between groups, but there were no differences in carotid blood flow at 1 hour after ROSC.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…While this first study used a CC rate of 120/min (in the CC + SI group) instead of the recommended 90/min, further studies using CC rates of 90/min in the same animal model have confirmed the initial findings [87][88][89][90]. Also a recent pilot trial in preterm infants <32 weeks' gestation showed similar results to the animal studies with a reduction in the mean (SD) time to ROSC with 31 (9) sec vs. 138 (72) sec in the CC + SI group and 3:1 C:V group (p = 0.011), respectively [91]. These data suggest that CC + SI has the potential to improve neonatal CPR, and a large randomized trial is currently ongoing to compare CC + SI with 3:1 C:V. Until these data are available, the 3:1 C:V ratio should be used during neonatal CPR.…”
Section: Chest Compressionssupporting
confidence: 71%
“…These studies suggest that during neonatal CPR, different C:V ratios do not improve outcomes and might not be the optimal CC approach in newborn infants. In comparison with the recommended 3: 1 C:V, combining CC with sustained inflation has been shown to be more effective in improving ROSC in piglets [15, 22-24], but not in lambs [25]. …”
Section: Discussionmentioning
confidence: 99%